Pengaruh Pemberian Cacing Darah (Chironomus sp.) Kering Terhadap Kecerahan Warna Ikan Guppy (Peocilia reticulata) - Lumbessy, Salnida Yuniarti; Ayuningsih, Evi; Lestari, Dewi Putri (Jurnal Sains dan Teknologi Perikanan, 2024)
This research aims to analyze the effect of adding natural blood worms (Chironomus sp) to the feed on the color of guppy fish (P. reticulate). The research was carried out for 50 days, at the Fish Production and Reproduction Laboratory, Mataram University using experimental methods with a completely randomized design (RAL ) consisting of 4 treatments and 3 repetitions, namely: A: Control feed (100%) B: 75% control feed and 25% dried blood worms C: 50% control feed and 50% dried blood worms and D: Control feed 25% and 75% dried blood worms. Test parameters include carotenoid content, brightness of fish color, absolute weight, specific growth rate, survival and water quality. Data were analyzed using Analysis of Variance (ANOVA) and continued with the Duncan test. The results of the research show that dried blood worms have the potential to be a source of natural carotenoids in increasing color brightness and do not have a negative impact on the growth and survival of guppy fish. The addition of up to 50% dried blood worms to the formulated feed was able to increase the color brightness of guppy fish with a Lightness (L*) value of 56.95, Redness (a*) of -0.09, Yellowness (b*) of 14.84 , Hue is 258.01 and Chroma value is 110.12